Haploidentical stem cell transplantation in patients aged 50 yr and older with leukemia: similar outcomes compared to younger adults. (27th April 2015) - Chen, Yao; Wang, Yu; Xu, Lan‐Ping; Liu, Kai‐Yan; Chen, Huan; Chen, Yu‐Hong; Zhang, Xiao‐Hui; Wang, Feng‐Rong; Han, Wei; Wang, Jing‐Zhi; Yan, Chen‐Hua; Zhang, Yuan‐Yuan; et al.
Abstract Aim We aimed to analyze the complications and survival associated with myeloablative haploidentical SCT in patients aged ≥50 yr and compare these results with a younger group population. Design and methods In this case–control study, enrolled patients with leukemia were identified from 1262 patients between May 2002 and May 2013 at a single institution. Results Thirty‐one patients were aged ≥50 yr (the older group) and 165 patients were aged 18–49 yr (the younger group). Of the older group, 20 of 31 (64.5%) had a hematopoietic cell transplantation comorbidity index (HCT‐CI) of 0 or 2. Statistical analysis showed no significant differences in the incidences of grades II to IV acute GVHD, extensive chronic GVHD, and non‐relapse mortality (NRM), or probability of relapse between the two groups. Furthermore, the 3‐yr overall survival (OS) and leukemia‐free survival (LFS) were not significantly different between the older and younger groups: 67.0 ± 9.3% vs. 75.3 ± 3.4% (p = 0.406) and 60.5 ± 9.6% vs. 72.5 ± 3.5% (p = 0.183), respectively. Conclusion Selected older patients aged ≥50 yr with low HCT‐CI and good performance status could safely undergo haploidentical SCT.